(untitled) (Fiep Bulletin - online, 2015)
The aim of this study is to analyze the imaginary constructions of physical education teacher’s regarding their future career’s meanings through the interpretation of the proverbs written on their university’s uniforms. The proverbs were grouped in five categories (magisterial, health, quality of life, fitness, professional legitimacy, humor) and they were analyzed under the theory of social imaginary proposed by Castoriadis (1980, 1997) and ethno methodology as seem in Coulon (1995) and Silva (1998).